EFFECT OF INJECTOR OPENING PRESSURE ON PERFORMANCE AND EMISSION OF LPG - METHYL ESTER OF MAHUA OIL DUAL FUEL ENGINE - N. Kapilan (Universitas Gadjah Mada, 2008)
One of variables, which affect the performance and emission of dual fuel engine is injection pressure. Hence in the present work, effect of Injector opening pressure on the performance of the engine was studied. A four stroke single cylinder engine was modified to work in dual fuel mode. Three injector opening pressures (180 bar, 200 bar and 220 bar) were considered for the present work. Methyl ester of mahua oil was used as pilot fuel and LPG was used as primary fuel. From the test results, it was observed that the injector opening pressure of 200 bar results in higher brake thermal efficiency. The higher injector opening pressure results in better atomization and peneatration of methyl ester of mahua oil. The exhaust emissions such as Smoke, unburnt hydro carbon and carbon monoxide of 200 bar is lower than other pressures.